Determination of the Total Phenolics Content and Antioxidant Activity of Extracts from Parts of Plants from the Greek Island of Crete - Eleftherios Kalpoutzakis; Theodoros Chatzimitakos; Vassilis Athanasiadis; Sofia Mitakou; Nektarios Aligiannis; Eleni Bozinou; Olga Gortzi; Leandros A. Skaltsounis; Stavros I. Lalas (Plants, 2023)
Oxidative damages are responsible for many adverse health effects and food deterioration. The use of antioxidant substances is well renowned, and as such, much emphasis is placed on their use. Since synthetic antioxidants exhibit potential adverse effects, plant-derived antioxidants are a preferable solution. Despite the myriads of plants that exist and the fact that numerous studies have been carried out so far, there are many species that have not been examined so far. Many plants under research exist in Greece. Trying to fill this research gap, the total phenolics content and antioxidant activity of seventy methanolic extracts from parts of Greek plants were evaluated. The total phenolics content was measured by the Folin–Ciocalteau assay. Their antioxidant capacity was calculated by the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) scavenging test, the Rancimat method based on conductometric measurements, and the thermoanalytical method DSC (Differential Scanning Calorimetry). The tested samples were obtained from several parts of fifty-seven Greek plant species belonging to twenty-three different families. Both a remarkably high phenolic content (with gallic acid equivalents varying between 311.6 and 735.5 mg/g of extract) and radical scavenging activity (IC50 values ranged from 7.2 to 39.0 μg/mL) were found in the extract of the aerial parts of Cistus species (C. creticus subsp. creticus, C. creticus subsp. eriocephalus, C. monspeliensis, C. parviflorus and C. salviifolius), Cytinus taxa (C. hypocistis subsp. hypocistis, C. hypocistis subsp. orientalis and C. ruber), and Sarcopoterium spinosum. Furthermore, the sample of Cytinus ruber showed the highest protection factor (PF = 1.276) regarding the Rancimat method, which was similar to that of butylated hydroxytoluene (BHT) (PF = 1.320). The results indicated that these plants are rich in antioxidant compounds, potentiating their use either as food additives to enhance the antioxidant properties of food products, or protect them from oxidation, or as sources for the preparation of food supplements with antioxidant properties.